2010
DOI: 10.7322/abcs.v35i3.78
|View full text |Cite
|
Sign up to set email alerts
|

Lombalgia gestacional: prevalência e características de um programa pré-natal

Abstract: ResumoIntrodução: A dor lombar é uma queixa comum na população em geral e é sintoma frequentemente relacionado à gestação. Esse sintoma é limitante, já que interfere diretamente nas atividades de vida diária (AVD) e qualidade de vida. Objetivo: Determinar a prevalência de lombalgia e descrever suas principais características em gestantes. Métodos: Quarenta e cinco gestantes do primeiro ao terceiro trimestre de gestação, assistidas pelo Programa de Pré-Natal do Ambulatório Municipal João Lânia, em José Bonifáci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
28

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 6 publications
3
5
0
28
Order By: Relevance
“…Studies (11,12,13,14) on the prevalence of gestational low back pain in our country have found results similar to ours, ranging from women had the first episode of pain after 14 gestational weeks, being compatible with most of the previous studies (3,4,8,27), possibly related to direct fetal pressure against the neural elements of the lumbar spine and greater overload in the lumbar muscles (13).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Studies (11,12,13,14) on the prevalence of gestational low back pain in our country have found results similar to ours, ranging from women had the first episode of pain after 14 gestational weeks, being compatible with most of the previous studies (3,4,8,27), possibly related to direct fetal pressure against the neural elements of the lumbar spine and greater overload in the lumbar muscles (13).…”
Section: Discussionsupporting
confidence: 81%
“…However, for pregnant women with low back pain, rest may be a strategy to relieve symptoms, since our study revealed that the majority (76.7%) found pain relief at bedtime, sit or relax, not related to lumbar incapacity. Previous studies (8,14) also reported improvement of the symptom with rest, possibly related to muscle relaxation (12), and worsened with the orthostatic position. Also, according to the participants, our study revealed that the walking, and this is significantly related to lumbar incapacity, possibly due to overload in the musculoskeletal system (14), but also, to the increase of the width of the step that consumes more energy and the longer time of maintenance of the feet on the ground, decreasing the simple support time, used as strategy for greater stability and support of body weight (25).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A dor lombar é queixa constante entre as gestantes. Neste estudo a prevalência foi em torno de 84,2% para o Grupo I e de 78,9% para o segundo grupo, dados que corroboram com outros resultados encontrados na literatura 7,8,17,19,20 . Não há uma causa específica que explique o surgimento da lombalgia gestacional, mas sugere-se que as alterações que ocorrem no corpo da mulher durante a gestação favoreçam o surgimento da lombalgia, contribuindo para o quadro doloroso 18 .…”
Section: Discussionunclassified
“…É uma das principais causas de incapacidade física durante a gestação, dificultando a realização de atividades da vida diária, o trabalho e atividades domésticas, além de prejudicar o sono e interferir na qualidade de vida dessas mulheres 8,9 . Assim, de acordo com a literatura, as gestantes têm relatado mais limitações devido a problemas emocionais, baixo nível de funcionamento físico, vitalidade e aspectos sociais quando comparadas a mulheres não grávidas 10 .…”
Section: Introductionunclassified